Genotypic Characterization of Avian Escherichia coli by Random Amplification of Polymorphic DNA - Gomes, Amitha R.; Muniyappa, L.; Krishnappa, G.; Suryanarayana, V.V.S.; Isloor, S.; Prakash, B.; Hugar, P.G. (International Journal of Poultry Science, 2005)
Fifteen serotypes of E. coli isolated from poultry were subjected to RAPD-PCR using eight oligonucleotide random primers. Amplification with each of the primers resulted in generation of different DNA fingerprinting profile with varied number of bands. Dendrogram based generation of clustering of E. coli serotypes showed two major clusters. The polymorphic amplicons served as markers for E. coli species where as the unique amplicons served as markers for E. coli serotypes. RAPD based fingerprinting provided a rapid means of discriminating E. coli serotypes and considered a valuable tool for molecular typing.